TRANSFORMASI MANAJEMEN LEMBAGA PENDIDIKAN MENENGAH ISLAM DALAM ERA DIGITALISASI PENDIDIKAN DI SMA IBA PALEMBANG - Rauzatul Jannah; Lailatussaadah Lailatussaadah (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to analyze the influence of public relations management courses on the communication competence of Islamic Education Management students of UIN Ar-Raniry Banda Aceh. A quantitative approach is used by collecting data through a questionnaire through a Google Form that has been validated by experts. The sample consisted of 92 students of the class of 2023 from a population of 125, determined based on the Krejcie and Morgan tables for proportional representation. The analysis was performed with Structural Equation Modeling Partial Least Squares (PLS-SEM) using SmartPLS, including convergent validity tests (outer loading >0.70, AVE >0.50), reliability (Cronbach's Alpha >0.70), and bootstrapping for path coefficients, T-statistics, and R-squares. The results of the data analysis found that the Public Relations Management and Public Relations course had a positive and significant effect on communication competence with a path coefficient of 0.817, T-statistics of 19.319 (p<0.001), and R-square of 0.668. Therefore, this course is effective in shaping students' communication competencies through applied learning.